Caracterização cinética da protease trômbica presente no veneno de "Bothrops leucurus": leucurobina. - Matheus Philippe Teixeira de Sena (2006)
It was obtained in this work more data about leucurobin, a snake venom thrombin-like enzyme from Bothrops leucurus, very common in Brazilian Northeast. The kinetic parameters KM, kcat, kcat/KM over p-nitroanilin chromogenic substrates was determined. The coagulant activity over citrated human plasma and purified bovine fibrinogen was evaluated. Leucurobin has amidasic activity over substrates with LArg in P1 position. The best chromogenic substrate was D-Phe-L-Pro-L-Arg-pNA. The amidasic activity over D-Phe-L-Pro-L-Arg-pNA was inhibited in presence of Na+, K+, Ca+2 and Mg+2. Leucurobin has strong coagulant activity in vitro over citrated human plasma and purified bovine fibrinogen. The coagulant activity in vitro over bovine fibrinogen was inhibbited in presence of Na+ and K+, but not in presence of Ca+2 and Mg+2.